Fishing Gear as a Data Collection Platform: Opportunities to Fill Spatial and Temporal Gaps in Operational Sub-Surface Observation Networks - Van Vranken, Cooper; Vastenhoud, Berthe M. J.; Manning, James P.; Plet-Hansen, Kristian S.; Jakoboski, Julie; Gorringe, Patrick; Martinelli, Michela (Frontiers in Marine Science, 2020)
While the open oceans are well covered by automated ocean measurement instruments, there is a lack of sub-surface oceanographic observation in coastal and shelf seas. Commercial fishing gear such as bottom trawls, pots, traps and long lines can act as a platform for sensors, which collect physical oceanographic data concurrently with normal fishing operations. The lack of observed in-situ ocean data in coastal and shelf seas limits operational oceanography, weather forecasting, maritime industries, and climate change monitoring. In addition, using fishing gear as an ocean observation platform has auxiliary benefits for fisheries management including stakeholder involvement. This study quantifies and compares the existing sub-surface in-situ data coverage with the spatial distribution of fishing activities. The results show that integration with fishing could contribute to filling some of the most pressing gaps in existing ocean observation systems in coastal and shelf seas. There are limitations inherent to opportunistic data collection, mainly related to spatial and temporal heterogeneity of fishing activities. However, we make the case that fishery-based observations have the potential to complement existing ocean observing systems in areas where oceanographic data are lacking and needed most in order to ensure long term sustainability of oceanographic monitoring.